DIGITALISASI PEMILIHAN E-VOTING KETUA RW: RWDIGI KOMPLEK SUKAASIH UJUNG BERUNG - Adhisti Dara Narda; Fikry Muhammad Ilham; Najwa Saira Permana; Sahdan Idam Khoir; Nayla Nuriyah Azzahra Winata (Setia Mengabdi: Jurnal Pengabdian kepada Masyarakat, 2022)
The means in democracy in Indonesia to realize a system of government that is sovereign by the people is by means of general elections, including the election of the RW chairman. The existence of the RW head is very important as a leader for the surrounding community. So from that appeared RWDIGI. RWDIGI is the election of RW heads with digitalization. RWDIGI emerged because of several problems encountered when electing RW heads in the conventional way. One of them is the use of a longer time. Therefore RWDIGI emerged as a way to minimize this. From this, this innovation resulted in support from the surrounding community and also provided an opportunity for STIA LAN Bandung Polytechnic students to become the committee for selecting the Chair of the RW. Digitalization innovations have brought significant changes by increasing performance and making interactions between individuals and groups easier. In addition, with digitalization, the process for selecting RW heads is more efficient and security and results are guaranteed.